Role of Trypanosoma cruzi nucleoside diphosphate kinase 1 in DNA damage responses - Reigada, Chantal (2020)
BACKGROUND NME23/NDPKs are well conserved proteins found in all living organisms. In addition to being nucleoside diphosphate kinases (NDPK), they are multifunctional enzymes involved in different processes such as DNA stability, gene regulation and DNA repair among others. TcNDPK1 is the canonical NDPK isoform present in Trypanosoma cruzi, which has nuclease activity and DNA-binding properties in vitro. OBJECTIVES In the present study we explored the role of TcNDPK1 in DNA damage responses. METHODS TcNDPK1 was expressed in mutant bacteria and yeasts and over-expressed in epimastigotes. Mutation frequencies, tolerance to genotoxic agents and activity of DNA repair enzymes were evaluated. FINDINGS Bacteria decreased about 15-folds the spontaneous mutation rate and yeasts were more resistant to hydrogen peroxide and to UV radiation than controls. Parasites overexpressing TcNDPK1 were able to withstand genotoxic stresses caused by hydrogen peroxide, phleomycin and hidroxyurea. They also presented less genomic damage and augmented levels of poly(ADP) ribose and poly(ADP)ribose polymerase, an enzyme involved in DNA repair. MAIN CONCLUSION These results strongly suggest a novel function for TcNDPK1; its involvement in the maintenance of parasite’s genome integrity.